2018
DOI: 10.1021/acs.accounts.7b00548
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Materials and Devices for Bioresorbable Electronics

Abstract: Recent advances in materials chemistry establish the foundations for unusual classes of electronic systems, characterized by their ability to fully or partially dissolve, disintegrate, or otherwise physically or chemically decompose in a controlled fashion after some defined period of stable operation. Such types of "transient" technologies may enable consumer gadgets that minimize waste streams associated with disposal, implantable sensors that disappear harmlessly in the body, and hardware-secure platforms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
123
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(123 citation statements)
references
References 48 publications
0
123
0
Order By: Relevance
“…in real-time [7,8] For health and medical applications there are additional requirements such as substrates should be disposable, dissolvable, bioresorbable and biocompatible etc. [9,10]. Such eskin patches could either be placed directly on body surface or on daily wearables such as clothes, watch or jewellery etc.…”
Section: What Is E-skinmentioning
confidence: 99%
“…in real-time [7,8] For health and medical applications there are additional requirements such as substrates should be disposable, dissolvable, bioresorbable and biocompatible etc. [9,10]. Such eskin patches could either be placed directly on body surface or on daily wearables such as clothes, watch or jewellery etc.…”
Section: What Is E-skinmentioning
confidence: 99%
“…[33] The authors investigated the dissolution rate of Si NMs (B-doped, 10 15 cm −3 , 200 nm thick) in PBS (1×) spiked with different concentrations of albumin (0.01-35 g L −1 ), Si(OH) 4 (0-300 mg L −1 ) and cations (Na + , Mg 2+ and Ca 2+ , 1 × 10 −3 m) at 37 °C. The increase of the protein concentration slowed down the dissolution rate due to augmented protein adsorption onto the NM surface; moreover, regardless of the concentration (and presence) of proteins, the dissolution rate reduced by increasing the concentration of Si(OH) 4 , consistently with the chemical equilibrium reported in Equation (1). Conversely, the presence of cations in the aqueous medium (i.e., PBS at pH 7.4, with 35 g L −1 of proteins at 37 °C) led to an accelerated dissolution rate, which was greater for divalent cations (namely, Ca 2+ and Mg 2+ ) with respect to monovalent cations (Na + ).…”
Section: Inorganic Semiconductorsmentioning
confidence: 99%
“…and 2) hydrolysis of silicon oxide, according to Equation (4). The overall reaction is reported in Equation (6)…”
Section: Silicon Oxides and Nitridesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the mechanical incompliance and the possibility of toxicity of inorganic materials, biodegradable polymers based on naturally derived poly mers and synthetic polymers became the field of intensive study. [135,136] In a recent review reported by Feig et al, taking an example of a typical transistor structure, it provided thorough materials design considerations for the individual degradable components, including but not limited to electrodes (e.g., corrodible metals such as Fe and Mg), substrates (e.g., polylactic-co-glycolic acid (PLGA)), dielectrics (e.g., poly(glycerol sebacate) (PGS)) and semiconductor films. [137] With the wide choices of materials to achieve degradability, research on transient wearable and skin-like electronics are expected to burgeon.…”
Section: Self-healing and Biodegradabilitymentioning
confidence: 99%